Design and analysis of a novel ship pipeline welding auxiliary device. (1st September 2016) - Huang, Haocai; Yuan, Zhuoli; Qian, Hongbao; Ye, Yanying; Leng, Jianxing; Wei, Yan
Abstract: Nowadays ship pipelines alignment and welding process play a dominant role in ensuring the assembly speed in shipbuilding processes and the operation reliability in ship commissioning processes. However, the pipeline welding quality relies heavily on the experiences of personnel of the shipyard, which further hinders the improvement of welding efficiency and accuracy. This paper develops a novel ship pipeline welding auxiliary device(SPWAD). It is driven by hydraulic cylinder and equipped with the wedge force amplifier mechanism and able to align, center and lock two welding pipelines more conveniently and reliably. The capability of the SPWAD in resisting welding stress was analyzed by finite element analysis in ANSYS Workbench, and the results shows that the SPWAD is capable of resisting the certain welding stress in extreme condition A series of shipyard experiments were conducted, which demonstrated that the maximum concentricity and non-parallelism of the welding pipeline is 0.481 mm and 2.615 mm respectively by using the SPWAD, and its practicability was also verified. The efficiency of ship pipeline welding with the SPWAD is estimated up to increase by about 5 times. Highlights: We develop a novel ship pipeline welding auxiliary device (SPWAD). SPWAD driven by hydraulic cylinder and equipped with the wedge force amplifier mechanism. The shipyard experiments demonstrated that the maximum concentricity and non-parallelism of the welding pipeline is 0.481 mm and 2.615 mm respectively by using the SPWAD The efficiency of SPWAD is estimated up to increase by about 5 times.